Impacts of land cover change on climate trend in Padang Indonesia - Dedi Hermon (Faculty of Geography, Universitas Gadjah Mada, 2014)
ἀe purpose of this study was to analyze the trend of climate change through changes in the elements of Green House Gases (GHGs), includes the trend of CO2, N2O, and CH4. ἀe change of the extreme rainfall and temperature indices due to land cover change into developed area in Padang. IdentiḀcation and analysis trends of climate change and extreme climatic events were analyzed by using RclimDex the Expert Team for Climate Change Detection and Indices (ETCCDMI) technique. Where as the analysis and interpretation of land cover changes into developed area used Landsat TM 5 and Landsat 1985 7 ETM + of 2011 by ERDAS 9.2 GIS with the supervised classiḀcation method and GIS Matrix. ἀe results of the study provide informations of land cover changes into developed area at forest land (11,758.9 ha), shrub (3,337.3 ha), rice Ḁelds (5,977.1 ha), and garden (5,872.4 ha). It has an implication on increasing of the ele-ments of GHGs concentration such as CO2 (14,1 ppm), N2O (5,4 ppb) and CH4 (24,8 ppb). ἀis condition lead to an extreme temperature and presipitation indexs trends in Padang.